Effect of Cellulose-Ibeta Presence in Sawdust on Compressive Strength of Cement Paste - Namdar, Abdoullah; Fadzil, Mat Yahaya (Canadian Center of Science and Education, 2014)
In this paper, enhancement of compressive strength of OPC paste is main objective. 1% and 4% of sawdust powder has been blended to Ordinary Portland Cement (OPC) paste. The compressive strength has been measured on 7, 28, 56 and 90 days. The micro properties of OPC paste has been investigated by using X-ray diffraction (XRD) and Atomic Force Microscopy (AFM). The best quantity for replacement of sawdust is 1%. The mixture of 4% sawdust to OPC paste has also been improved compressive strength of concrete. The cellulose-Ibeta presences in saw dust, has been modified the surface roughness and hydration of OPC paste, and leads to enhancement of compressive strength of concrete. The compressive strength of OPC paste has been stabilized with increase of age, due to pozzolanic actions. The compressive strength of OPC has been decreased with increase sawdust contents.